A Comprehensive Analysis of the Need for Gender‑Neutral Laws and Judi‑ cial Responses to Women‑Centric Bias - Gupta, Shivangi (Trinity Law Review, 2026)
The evolution of gender justice in India has historically been shaped by women-centric legal reforms aimed at addressing entrenched patriarchal norms, domestic violence, sexual exploitation, and systemic discrimination. Legislative frameworks such as the Protection of Women from Domestic Violence Act and gender-specific provisions under criminal law were indispensable in responding to widespread gender-based violence and inequality. However, contemporary social realities reveal significant limitations within these protective regimes. Increasing allegations of misuse, the emerging recognition of violence against men, the absence of adequate remedies for transgender and LGBTQ+ persons, and the judiciary’s emphasis on individual autonomy and equality have reignited debates on the need for gender-neutral legal structures.This paper undertakes a comprehensive doctrinal, analytical, and comparative examination of India’s criminal and civil laws through a gender-neutral lens. It critically evaluates women-centric statutes, analyzes judicial acknowledgment of their misuse, examines the constitutional permissibility of sex-based classifications, and identifies structural exclusions that deny equal legal remedies to male, transgender, and non-binary victims. Further, the study compares Indian jurisprudence with gender-neutral legal frameworks in jurisdictions such as Canada, the United Kingdom, Australia, and New Zealand to identify global best practices that balance victim protection with safeguards against wrongful prosecution.The paper concludes that while women continue to require robust legal safeguards against gender-based violence, an equitable and modern justice system must extend protection and accountability mechanisms to all individuals irrespective of sex or gender identity. It argues for recalibrated, gender-neutral legal reforms that uphold constitutional morality, reinforce substantive equality, and promote an inclusive and balanced model of justice in contemporary India.
Keywords: evolution; justice; large ly; shaped; patriarchal